Physicochemical Characteristics and Sensory Evaluation of Mixed-Fruit Leather - Ho, Lee-Hoon; Suhaiba Shafii, Nur; Shahidan, Norshazila (International Journal of Engineering and Technology, 2018)
The objective of the present study was to investigate the physicochemical characteristics and sensory acceptance of mixed-fruit leather prepared from bananas, pineapples, and watermelons. Four different compositions of mixed-fruits (Control = 33 g banana + 33 g pineapple + 33 g watermelon; 50B = 50 g banana + 25 g pineapple + 25 g watermelon; 50P = 50 g pineapple + 25 g banana + 25 g watermelon; 50W = 50 g watermelon + 25 g banana + 25 g pineapple) were produced. The results from the proximate analysis showed that mixed-fruit leather 50B contained higher moisture, crude protein, and crude fat compared to other samples. The highest carbohydrate content was recorded in sample 50P. Water activity of all mixed-fruits leathers were lower than 0.5. The lowest pH (4.01) and the highest total titratable acidity (0.14) were recorded in sample 50P. A 50P mixed-fruit leather possessed the highest L* and b* values whereas 50W had the highest a* value. The textural properties of all samples were not significantly different. All mixed-fruit leathers were accepted by the panellist. The results obtained from the present study showed that mixed-fruit leather has the potential to be produced as a healthy snack.Â